Durkheim’s Effervescence and Its Maussian Afterlife in Medical Anthropology - Hsu, Elisabeth (2017)
What, if not Durkheim’s ‘collective representations’ acquired during exalted states of effervescence, gives rise to society, culture and science? Marcel Mauss provides another answer by pointing to the different rhythms of social relationships and the human effort to synchronise them. The seasonal cycle of the Eskimo [Inuit], Mauss argues, is in accord with their game; hence people disperse in summer to pursue economic activities in small bands, while they congregate in dense house-complexes in winter and engage in ritual. It would appear that Mauss draws heavily on Boas’s contrast between the Kwakiutl winter celebrations and their ‘uninitiated’ livelihood in summer. These insights have traction for medical anthropologists who are interested in finding an anthropological explanation for the efficaciousness of ‘traditional’ medicines or ‘indigenous’ healing techniques.